Comparative Analysis of Differentially Expressed Circular RNAs in Polarized Macrophages - Zhou, Rong-mei; Shi, Ze-hui; Shan, Kun; Zhang, Shu-jie; Zhang, Yi-han; Liang, Yu; Yan, Biao; Zhao, Chen (Frontiers in Genetics, 2022)
Macrophage polarization is a process that macrophages exert different functions according to surrounding micro-environment. Macrophages commonly exist in two distinct subsets: classically activated M1 macrophages and alternatively activated M2 macrophages. Circular RNAs (circRNAs) are a novel class of non-coding RNAs generated by back-splicing. Thousands of circRNAs were identified in different cells and tissues. Recent studies have revealed that circRNAs play a crucial role in regulating transcriptional and post-transcriptional gene expression. However, the effects and roles of circRNAs in macrophage polarization haven’t been well elucidated. Here, circRNAs expression profiles were determined in human THP-1 macrophages incubated in conditions causing activation toward M1 (interferon-γ + LPS) or M2 (interleukin-4) phenotypes. Overall, 9,720 circular RNA were detected from RNA sequencing data. Compared with M2 macrophages, a total of 140 circRNAs were aberrantly expressed in M1 macrophages, including 71 up-regulated circRNAs and 69 down-regulated circRNAs. Quantitative real-time PCR (qRT-PCR) results were generally consistent with the selected differentially expressed circRNAs. Gene Ontology (GO) and KEGG pathway analyses were used to predict biological functions and potential mechanisms of the host linear transcripts of these up-regulated and down-regulated circRNAs. Furthermore, we found that the expression level of circRNA-RNF19B (circRNF19B) in M1 macrophages was significantly higher than that in THP-1 macrophages and M2 macrophages. circRNF19B expression was increased when M2 converted to M1 whereas decreased when M1 converted to M2. Knockdown of circRNF19B following the activation of THP-1 cells using interferon-γ + LPS diminished the expression of M1 macrophages markers and elevated the expression of M2 macrophages markers. In conclusion, these data suggest the involvement of altered circRNAs expression patterns in macrophages exposure to different activating conditions. Circular RNAs may play important roles in regulating macrophage polarization.